Estimation of the In-Vitro Synergistic Effect of Vancomycin with Bacteriophage and its Endolysin on Iraqi Local Isolates of Enterococcus faecalis - Rand R. Hafidh; Zainab Oday Hamed; Abdullah A. Awni; Manal N. Jassas (مجلة بغداد للعلوم)
Enterococcus faecalis is known to cause many serious infections with an upsurge in the development of antibiotic resistant strains, especially vancomycin. Lytic bacteriophage and its endolysin have the potential to affect and lyse specific bacterial cells making them a possible alternative therapy to antibiotic resistant strains. The study aimed to investigate the synergistic effect of phage/ phage cocktail/ endolysin with vancomycin on E. faecalis isolated from urine samples. The antibioresistant profile 17 E. faecalis was done with an emphasis on the sensitivity to vancomycin. The lytic phages were isolated from the local environment. The infectivity and the coverage rate for the phage and phage cocktail were calculated. The enzyme of the lytic phage was isolated by chromatography. The synergistic effect was tested by turbidity reduction assay to evaluate the growth reduction level. It had been found that 6/17 E. faecalis isolates were resistant to vancomycin, 7/17 isolates were intermediate, and 4/17 were susceptible. Three lytic phages were identified with an infectivity rate of 100%, 76.4%, and 88.2%. The phage cocktail yielded 100% rate of infectivity and 91.6 % coverage rate. The reduction in the growth levels of the 17 E.faecalis after treatment with phage / phage cocktail/ vancomycin/ mixture of vancomycin and phage cocktail was effective. The synergistic effect of vancomcyin together with the phage cocktail significantly reduced the growth of 70.6% of the isolates. The antibacterial activity of vancomycin plus endolysin treatment was revealed in a time dependent manner. Thus, the synergistic effect of vancomycin with phage/ endoloysin illustrated an effective method to treat the antibiotic-resistant strains of E. faecalis to overcome this emerging clinical problem.